Facile and accelerated production of RuO2 monolayers via a dual-step intercalation process. Issue 6 (26th February 2020) - Kim, Se Yun; Shin, Weon Ho; Jung, Doh Won; Ko, Dong-Su; Roh, Jong Wook; Hwang, Sungwoo; Lee, Jongmin; Lee, Kimoon; Park, Hee Jung; Kwak, Chan; Kim, Sang-il; Jeong, Hyung Mo; et al.
Abstract : RuO2 monolayer nanosheets were prepared by a rapid and efficient dual step exfoliation process. Abstract : Tetrabutylammonium ions (TBA + ) have commonly been used to exfoliate RuO2 into monolayers via ion exchange reactions. However, the low production yield of RuO2 exfoliation, which originates from the large molecular size of TBA +, limits wider utilisation of RuO2 monolayers in optoelectronic applications. We introduce a rapid and efficient dual-step exfoliation process beginning with intercalation of small organic molecules (tetramethylammonium ions) into RuO2, which is followed by the addition of TBA + as a second intercalant to realize RuO2 monolayer production. Our dual-step intercalation process increases the RuO2 monolayer exfoliation yield from 9.9% to 60% after 14 days. Density functional theory calculations reveal that the activation energy of dual-step intercalation is much lower than that of direct intercalation of TBA + ions into the RuO2 structure. The experimental and theoretical results of dual-step intercalation suggest that it is a facile and general approach for the production of metal oxide monolayers, and could widen the use of metal oxide monolayer nanosheets.